CONCORDANCE OF TECHNOGENESIS WITH ECODEVELOPMENT - S. M. Sukhorukova; A. M. Pogorelyi; S. G. Vysotskiy (Российский технологический журнал)
In the conditions of industrial production for profit-making it is necessary to make as much products as possible in a time unit. In this regard technological equipment it is more preferable to the businessman than the human, because the equipment does not care how much the natural environment degrades after its use. It means that the vector of technological development motivated by profit is not connected with preservation of the environment suitable for the human. In order to overcome this orientation it is necessary that the economic motivation of using new technologies would not allow ecologically negative consequences of their introduction. However, it is not so in the conditions of market economy. Today the cause of environmental problems is rightly connected with the equipment and technologies developed on the basis of achievements of modern science. However, one should not understand by this only the complex of engineering and natural-science knowledge. A considerable share of responsibility falls on human sciences including economic ones. For ecological safety of production it is necessary to develop a theory of economy orienting the technological development to coordination with the laws of the environment keeping its appropriateness for the life of the human. The article describes how the theory of market economy initially causes a mismatch of technogenesis and ecodevelopment, which determines the inevitability of emergence of environmental problems. In order to coordinate technogenesis with ecodevelopment and guarantee ecologically sustainable development, refusal of market economy is required, because this will allow to introduce long-term economic responsibility for ecological damage and to take into account changes in environmental management efficiency by using natural science knowledge on the basis of forecasts of cyclic changes in the biosphere.